EKSTRAKSI PEKTIN POD HUSK KAKAO SECARA KERING MENGGUNAKAN ASAM KLORIDA PADA BERBAGAI KONSENTRASI LARUTAN - Saputra, Adhi; Hutomo, Gatot Siswo; Rahim, Abdul (AGROTEKBIS, 2017)
The research aimed to gain the characteristic of pectin from dry cacao pod husk and the best physical or chemical quality of pectin resulted from dry extraction of cacao pod husk by using hydrochloric acid at the best concentration. This research used Completely Randomized Design under one single factor consisting of 5 treatments of concentration of solution, i.e 0.5 M, 1 M, 1.5 M, 2 M, 2.5 M which were replicated 4 times so that 20 units of experiment were obtained. The treatment with significant or very significant affect was then tested with Honest Significant Difference (HSD) test on the level of 5% or 1%. It was then analyzed with derivatives of quadratic functions formula to produce the best treatment of extraction of concentration of solution. The research reveal that the best pectin extraction was obtained at concentration of HCl 1.50 M with 15.09% of rendement value, 69.11% of methoxyl content, 54.56% of galacturonic acid and 68.24% of pectin clarity. Based on those findings, it can be concluded that HCl 1.50 M concentration is very good to extract the pectin from dry cacao pod husk with hydrochloric acid.Â Key Words: Cacao Pod Husk, Concentration of solution, Hydrochloric acid, pectin.